2021
DOI: 10.1590/s1517-707620210001.1220
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do tratamento térmico de alívio de tensão e do preaquecimento na microestrutura e microdureza da interface entre depósitos de inconel 625 e aços AISI 8630M e AISI 4130

Abstract: RESUMO O objetivo deste trabalho foi avaliar o efeito da aplicação de tratamento térmico de alívio de tensão (TTAT) e das temperaturas de preaquecimento e de interpasse sobre a microestrutura, presença de zonas parcialmente diluídas (ZPD), a microdureza e o gradiente de composição ao longo da interface de depósitos da liga AWS E NiCrMo 3 sobre os aços AISI 8630M e AISI 4130 aplicados por dois processos de soldagem (GMAW e PTA-P). Para isto foram executadas camadas sobrepostas de cordões de solda, utilizando di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…It is observed that sample 4, Figure 7, presented differentiated morphologies called "peninsula" and "islands" swirl patterns, at the interface between the WM (Weld Metal) and the BM (Base Metal) [38,39]. These grains are part of the so-called Partially Diluted Zone (PDZ) which is characterized by the penetration of WM into the BM [40,41]. Such morphologies were also presented in previous studies [32,39,42].…”
Section: Microstructural Analysissupporting
confidence: 65%
“…It is observed that sample 4, Figure 7, presented differentiated morphologies called "peninsula" and "islands" swirl patterns, at the interface between the WM (Weld Metal) and the BM (Base Metal) [38,39]. These grains are part of the so-called Partially Diluted Zone (PDZ) which is characterized by the penetration of WM into the BM [40,41]. Such morphologies were also presented in previous studies [32,39,42].…”
Section: Microstructural Analysissupporting
confidence: 65%